Relationship between occupied form of nuclear estrogen receptor and cytosolic progesterone receptor or DNA synthesis in uteri of estradiol implanted rats (Revista Española de Fisiología, 1987)
The effect of 17 beta-estradiol (E2) implantation on the cytosolic progesterone receptor (RcP), DNA and occupied form of nuclear estrogen receptor (o- Rn) content in the uterus of ovariectomized adult rats, is described.Animals were implanted with oil or E2-oil solution in Silastic capsules.The latter group animals were divided into two subgroups: in subgroup (a), capsules remained in situ until decapitation time.In subgroup (b) they were removed 48 h after implantation.The E2 implantation caused a significant increase in uterine weight, RcP and o-Rn content 48 h later.However, the DNA content increased significantly only after 72 h, but there was no significant difference in the t-Rn concentration in relation to the non-estrogenized animals.In subgroup (a) animals, these values remained unchanged until 96 h.In subgroup (b), the removal of E2 implants 48 h later caused an almost complete return to the values before the E2 implantation in terms of uterine weight, RcP and o-Rn content.However the DNA concentration remained higher and the t-Rn level was lower than those values that were obtained for the non- estrogenized rats.These results suggest that the RcP and DNA synthesis induced by E2 would be connected to the level of o-Rn, although a closer dependency over time seems to exist between the o-Rn and RcP levels than between the o-Rn and DNA concentrations.